Stress distribution in occlusal veneers with different finish lines when applying vertical and tangential forces = Distribución de estrés en carillas con diferentes líneas de terminación aplicando fuerzas verticales y tangenciales - Aliaga, Jimmy; Caro M., Rosa S.; Hermoza, Mónica (2022)
To evaluate stress distribution when applying vertical and tangential forces to 1mm thick occlusal veneers with different finish lines preparations, using the finite element method. One extracted third molar was prepared for occlusal veneers, firstly without any bevel. It was scanned in order to design two groups of lithium disilicate (G1A, G2A) and composite resin (G1B, G2B) occlusal veneers. Then, the third molar preparation was modified, beveling the finish line and it was subsequently scanned again to design the occlusal veneer groups with bevel (LD: G3A, G4A and CR: G3B, G4B). The four groups were subjected to different forces (400 N vertical and 900 N tangential). At 400 N, the non-beveled veneers showed slightly higher Von Mises stress values (G1A: 783 MPa and G1B 736.5 MPa) than the beveled veneers (G3A: 685.7 MPa and G3B: 675.8 MPa). However, when 900 N tangential forces were applied, the beveled occlusal veneers showed higher Von Mises stress values (G4A: 4297 MPa and G4B: 4133 MPa) than the non-beveled occlusal veneers (G2A: 2581.1 MPa and G2B: 3519.1 MPa). Furthermore, it was observed that the tissue under the occlusal veneers with bevel showed higher Von Mises stress values than the models without any bevel. Beveled and non-beveled occlusal veneers of lithium disilicate and composite resin presented similar stress distribution values when vertical forces of 400 N were applied; whereas with tangential forces of 900 N applied near to the finish line, the beveled groups presented notably higher stress values than the non-beveled groups. However, both finish line preparations presented adequate values for possible clinical performance.
Evaluar la distribución de estrés al aplicar fuerzas verticales y tangenciales en carillas oclusales de 1mm de espesor con diferentes líneas de terminación marginal por el método de elementos finitos. Se preparó un tercer molar extraído para carilla oclusal, primero sin bisel. Se escaneó para diseñar dos grupos de carillas oclusales de disilicato de litio (G1A, G2A) y resina compuesta (G1B, G2B). Después, esta preparación molar fue modificada, biselando la línea de terminación y escaneándola nuevamente para diseñar los grupos de carillas oclusales con bisel (DL: G3A, G4A and RC: G3B, G4B). Los 4 grupos fueron sometidos a fuerzas diferentes (400 N vertical y 900 N tangencial). Con 400 N, las carillas sin bisel presentaron ligera mayor tensión de Von Mises (G1A: 783 MPa y G1B 736.5 MPa) que las carillas con bisel (G3A: 685.7 MPa y G3B: 675.8 MPa). De distinta forma, al aplicar fuerzas tangenciales de 900 N, las carillas oclusales con bisel presentaron mayor tensión de Von Mises (G4A: 4297 MPa y G4B: 4133 MPa) que las carillas oclusales sin bisel (G2A: 2581.1 MPa y G2B: 3519.1 MPa). Además, se observó que los tejidos subyacentes a las carillas oclusales con bisel, presentaron mayor tensión de Von Mises, frente a los modelos sin bisel. Las carillas oclusales con y sin bisel de disilicato de litio y resina compuesta presentaron una distribución de estrés similar con fuerzas verticales de 400 N, por otro lado, con fuerzas tangenciales de 900 N, los grupos con bisel presentaron notablemente mayor tensión que los grupos sin bisel. Sin embargo, ambos diseños de terminación marginal presentaron valores adecuados para un posible desempeño clínico.
En revista Odóvtos, vol. 24, no. 3 (septiembre-diciembre 2022)
Descripción basada en el contenido visto el 05 de diciembre, 2024
También disponible en formato HTML y EPUB